Banana blossom as a local resource-based emergency food innovation fusion food product - Bridha Risya Ladiva; Putri Dias Pratami; Priatini Woro; Sabila Salwa Siti; Tsaniah Ilmiati; Insani Hurry Mega (E3S Web of Conferences)
This research aims to explain the innovation of emergency food products based on “Fusion Food” which uses banana blossoms as the main ingredient. Banana blossoms, a local and underutilized ingredient abundant in tropical regions, are the focus. In the context of food crises and natural disasters, innovation in emergency food products becomes increasingly important. The study combines banana blossoms with various ingredients to create a nutritious, long-lasting emergency food. Researchers conducted experiments in processing banana blossoms and combining them with other ingredients with interesting flavors and textures. The results of the research on the experimental design tested three formulations in organoleptic tests on 30 semi-trained panelists to see the level of preference (hedonics) for one of the recipe formulations. The Banana Heart Samosa SJP2 received the highest preference score of 4.14. The frozen banana blossom samosas have a shelf life of over three months, with optimal consumption within three months. Half-cooked samosas last less than three days in the refrigerator, under nine hours unrefrigerated, and cooked samosas last less than two days. This research highlights the significance of innovative emergency food products that meet nutritional needs and offer diverse flavors, potentially enhancing food security during emergencies.